Exploring eating disorder risk among Thai transfeminine youth: a comparative study with cisgender females - Nadvadee Aungkawattanapong; Orapa Suteerojntrakool; Thitaporn Prownpuntu; Chansuda Bongsebandhu-phubhakdi (Journal of Eating Disorders, 2024)
Abstract Background Adolescents, particularly vulnerable during puberty, often face heightened concerns about dieting and body image. Transfeminine youth, especially in Asian cultures, are understudied in this context. This study investigates eating disorder risks among Thai transfeminine youth and compares to cisgender females, focusing on the association with body dissatisfaction. This study aims to explore 3 objectives: (1) to assess and compare the prevalence of eating disorder risks between Thai transfeminine youth and cisgender females; (2) to examine the link between body dissatisfaction and eating disorder risks; (3) to identify risk factors associated with abnormal eating disorder screening outcomes. Method This is a cross-sectional comparative study conducted between September 2021 and October 2022. The study questionnaire includes Thai version of the Eating Attitude Test-26 (EAT-26) to assess the risks of eating disorders and Thai version of the Body Image Concern Inventory (BICI) to assess body dissatisfaction. The questionnaire was distributed through social media platforms to transfeminine and cisgender females, aged 12–25 years. The correlation between eating disorder risks and body dissatisfaction was analyzed with linear regression, while the comparisons between transfeminine individuals and cisgender female groups were analyzed with Wilcoxon rank-sum test. Results The study included 241 transfeminine individuals and 388 cisgender females, median age 19.0 years (interquartile range [IQR] 18–21) and 18 years (IQR 16–20), respectively. Ninety (37.3%) transfeminine individuals had an EAT-26 score ≥ 20, suggesting concerns for dieting and eating behaviors, compared to 70 (18%) cisgender females (p < 0.001). Risk factors for EDs included obesity (odds ratio [OR] 3.22, confidence interval [CI] 1.36–7.6) and low income (OR 3.66, CI 1.59–8.4). Protective factors were negligible exercise (OR 0.24, CI 0.09–0.66), gender identity disclosure (OR 0.27, CI 0.1–0.77), and high levels of happiness (OR 0.85, CI 0.73–0.98). There is a significant correlation between the positive eating behavior screening and the body dissatisfaction scores. Conclusions Transfeminine youths show significantly higher concerns about dieting, body weight, and eating behaviors than their cisgender females, highlighting the unique challenges they face. These results emphasize the needs for targeted screening, health care access for treatment and support for eating disorders in transfeminine youths.